Sadeq Hedayat: his life and works - Katouzian, H (Oneworld, 2008)
Sadeq Hedayat was born on 17 February 1903 and died on 9 April 1951. He was descended from Rezaqoli Khan Hedayat, a notable 19th century poet, historian, and historian of Persian literature, and author of Majma‘ al-Fosaha, Riyaz al-‘Arefin and Rawza al-Safa-ye Naseri. Many members of his extended family were important state officials, political leaders and army generals, both in the nineteenth and twentieth centuries.